Experimental Analysis and Control of a Wind-Generator System through a DC-DC Boost Converter for Extremum Seeking - Ahmed, T.; Baloch, M. H.; Khan, N.; Mehr, G.; Mirjat, B. A.; Memon, Y. A. (Engineering, Technology & Applied Science Research, 2021)
The advancement in technology has significantly improved the living standard, having a direct impact on the quality of life, at the cost of ever-increasing energy demand. Renewable energy resources such as the Wind Energy Conversion System (WECS) provide variable power generation. The current paper presents the results of the experimental analysis on the control of the wind-generator system based on SCIG through a dc/dc boost converter for extremum power-seeking. Since the Squirrel Cage Induction Generator (SCIG) is widely used in wind industries for power generation, their performance will be compared. The proposed system can operate either on a variable or at a nearly constant speed, with higher load capacity, while its power consumption is comparatively lower. The research will enhance the wind power at different wind speeds, to acquire the extremum power point tracking system from the wind power energy system by using two different machines.